Seismic risk assessment and intervention prioritization for Italian medieval churches. (November 2021) - Pirchio, David; Walsh, Kevin Q.; Kerr, Elizabeth; Giongo, Ivan; Giaretton, Marta; Weldon, Brad D.; Ciocci, Luca; Sorrentino, Luigi
Abstract: Rapid seismic risk assessments are critical to help practitioners, facility stakeholders, architectural heritage superintendence, and insurance companies in their asset management decision-making processes. In particular, the integrity of the Italian church portfolio has often been threatened by earthquakes. The Italian church portfolio includes thousands of religious buildings, representing pivotal facilities for the religious community, thus requiring an assessment methodology which accounts for the structural, architectural, cultural, and functional facets of churches. The methodology proposed herein combined both widely applied assessment techniques regarding structural vulnerability (e.g., "macro-blocks") with a newly developed framework accounting for other important variables (e.g., the heritage significance of a church) to produce a rapid, quantifiable, and holistic approach to determine the relative seismic risk assessment of historic masonry churches. On-site surveys of 72 unreinforced masonry medieval churches across Italy were conducted. Following a hierarchical approach for the surveys, each risk component – hazard, vulnerability, exposure, and consequence – was defined throughout by the development of 13 different indices. Using the fuzzy set theory, the indices were aggregated into a final risk rating framework useful to provide stakeholders with a scientific-based prioritization list for the maintenance and strengthening intervention of their church portfolios. Highlights: Holistic seismic risk assessment for historic unreinforced masonry churces Definition of risk indices for each risk components (i.e., hazard, vulnerability, exposure, and consequences) and their subcomponents. Application of fuzzy set theory to risk assessment. Definition of ready-to-use equations to determine the indices of risk based on easily accessible information. Prioritization for the strengthening and/or retrofitting intervention on historic buildings.